Effect of organic sources of plant nutrients on yield, quality and nutrient uptake in onion - Shine, KG; Bhalekar, MN; Pawar, PK; Patil, BT (Vegetable Science, 2017)
Onion (Allium cepa L.) is an important commercial crop grown worldwide. Now-a-days organically grown vegetables have more consumer acceptance and there is increasing demand of organically grown products. Organic farming is one among the broad spectrum of production methods that are supportive of the environment. Organic production systems are based on specific standards precisely formulated for food production and aim at achieving agro-eco systems, which are socially and ecologically sustainable. It is based on minimizing the use of external inputs through use of onfarm research efficiently compared to conventionalfarming. Thus the use of synthetic fertilizers and pesticides is to be avoided (Sivaraman 2007). Organic manures play an important role in improving soil physical, chemical and biological properties. The adoption of vermicompost helps in minimizing use of chemical fertilizers to the extent of 25-50% and increases the crop yield by 15-20% due to increased supply of essential elements (Marinari et al. 2000 and Singh et al. 2013)